Brain Organoid Transplantation: A Comprehensive Guide to the Latest Advances and Practical Applications—A Systematic Review - Yu-Ping Shen; Zaal Kokaia (Cells, 2025)
Brain organoid technology has seen significant development in recent years. This self-organized, three-dimensional, organ-oriented brain tissue model can recapitulate the process of neurogenesis and consists of diverse cell types and cellular architecture. Transplanting brain organoids in vivo could be a potential tool from bench to clinical research and has been studied for many purposes. To investigate and summarize the methodology, findings, and applications of this novel technique from current evidence, we conducted this systematic review by searching PubMed and the Embase databases for the literature ranging from 2013 to 2024. A total of 480 articles were identified, and 24 of them met the inclusion criteria. The results revealed that brain organoid transplantation had promising graft survival, neural proliferation, differentiation, and maturation, axonal growth, and functional integration into the host neuronal circuit, and has been applied to multiple applications, such as therapeutic usage, cell study platforms, and disease modeling. However, heterogeneity among studies, some significant challenges, and ethical issues remain to be considered. This comprehensive review will provide an update of what is known about this powerful, innovative method and discuss some practical aspects for future research.